2016
DOI: 10.1371/journal.pbio.1002578
|View full text |Cite
|
Sign up to set email alerts
|

A Normalization Framework for Emotional Attention

Abstract: The normalization model of attention proposes that attention can affect performance by response- or contrast-gain changes, depending on the size of the stimulus and attention field. Here, we manipulated the attention field by emotional valence, negative faces versus positive faces, while holding stimulus size constant in a spatial cueing task. We observed changes in the cueing effect consonant with changes in response gain for negative faces and contrast gain for positive faces. Neuroimaging experiments confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
50
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 72 publications
(101 reference statements)
10
50
2
Order By: Relevance
“…While some discrepancies between the putative mechanisms are likely due to differences in stimulus display properties, task designs and methods of measuring neural activity [15,4548,6971], we show here that another important factor is the duration of training. Similar to previous studies, we found that early in training, attentional gain of the visual P1 component accurately predicted attention-induced behavioral benefits [9,19,31].…”
Section: Discussionmentioning
confidence: 72%
“…While some discrepancies between the putative mechanisms are likely due to differences in stimulus display properties, task designs and methods of measuring neural activity [15,4548,6971], we show here that another important factor is the duration of training. Similar to previous studies, we found that early in training, attentional gain of the visual P1 component accurately predicted attention-induced behavioral benefits [9,19,31].…”
Section: Discussionmentioning
confidence: 72%
“…Attention is the main mechanism that controls this selection process. Numerous studies have demonstrated that attentional selection can be based on either a visual feature (Liu et al, 2007; Maunsell and Treue, 2006; Saenz et al, 2002; Serences and Boynton, 2007; Treue and Martinez-Trujillo, 1999; Zhang and Luck, 2009) or a spatial location (Brefczynski and DeYoe, 1999; Corbetta and Shulman, 2002; Kanwisher and Wojciulik, 2000; Kastner and Ungerleider, 2000; Martínez et al, 1999; Posner et al, 1980; Tootell et al, 1998; Zhang et al, 2012, 2016). Increasing evidence has indicated that attentional selection can also be deployed to entire objects: specific objects can be selected by directing attention to their features or to their locations (Scholl, 2001; Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using quantitative modeling suggest that there are several candidate mechanisms that can link attentional modulations in visual cortex with attentional modulations of behavior (14,25,26,33,50). While some discrepancies between the putative mechanisms are likely due to differences in stimulus display properties and task designs (15,41,(65)(66)(67) and methods of measuring neural activity (14,42,43,65), we show here that another major factor is the duration of training. Going beyond previous studies of training that have shown changes in attentional modulations, we quantitatively modeled the relationship between neural activity and behavior to systematically examine the relative contributions of different attention mechanisms (68)(69)(70)(71)(72).…”
Section: Discussionmentioning
confidence: 57%